Group A Streptococcus Infections in Children: Epidemiological Insights Before and After the COVID-19 Pandemic - Eleni Karapati; Andreas G. Tsantes; Zoi Iliodromiti; Theodora Boutsikou; Styliani Paliatsiou; Aglaia Domouchtsidou; Petros Ioannou; Vasileios Petrakis; Nicoletta Iacovidou; Rozeta Sokou (Pathogens)
Group A streptococcus (GAS) is the cause of both mild and invasive infections in humans with a high morbidity and mortality rate. The transmission of disease usually occurs via droplets, so the implementation of infection mitigation strategies (IMS) during the COVID-19 pandemic altered the incidence of GAS infection. This review aims to provide an overview of the influence of the COVID-19 pandemic on the incidence of GAS infection in children (invasive or non-invasive). A surge in the incidence of invasive GAS infection was noted in December 2022 after the reversal of IMS. A global uprise in GAS infection (invasive and non-invasive) was noted, especially concerning the pediatric population. Children younger than 5 years old were mostly affected, with complicated pneumonia being the leading clinical manifestation, causing many deaths worldwide. Emm1, specifically M1UK, was recognized as the dominant lineage in Europe and correlated with invasive disease. Healthcare professionals need to be alert about the severity of GAS-related infections, leading to early identification and treatment.